Thermodynamics of DNA with hump Morse potential - Gutiérrez, Hernán C.; Filho, Elso Drigo [UNESP]; Ruggiero, José R. [UNESP]; Gutierrez, Milton C.; Rivera, Liv C. F. (My University, 2016)
The thermal denaturation of DNA, i.e. the separation of the two strands is a phenomenon caused by the amplitude of the vibrations of the bases, therefore it is necessary to know how such separation is generated in order to implement alternative model of the melting behavior as a function of nucleotide sequence and therapies to combat the cancer. We propose to use the extended nonlinear Peyrard-Bishop(PB) model of DNA to include an anharmonic potential representing the aromatic stacking interaction between n- A nd (n-1)-th consecutive base pairs to treat the problem. We use Finite-difference methods for determine the mean value of the displacement for the hump Morse potential of the Peyrard-Bishop model of DNA. We show how the extended pseudoSchrödinger combined with finite difference method can be used to obtain the mean value displacements for the thermal denaturation of DNA with hump Morse potential.
Keywords: Finite-difference methods; Hump Morse potential; Pseudo-Schrödinger equation